PERAN GURU DALAM PENDIDIKAN MULTIKULTURAL PADA PENGEMBANGAN SIKAP TOLERANSI SISWA SD NEGERI 1001 BATANG BULU - Amir Hamzah Pulungan; Irma Sari Daulay; Hopman Daulay (CV. ADIBA AISHA AMIRA, 2023)
This study aims to determine the role of teachers in multicultural education in developing tolerance attitudes and supporting and inhibiting factors for teachers in developing tolerance attitudes of SD Negeri 1001 Batang Bulu students. The type of research used in this research is qualitative descriptive. The descriptive approach is research to make awareness systematically, factually, and accurately about the facts and properties of the population in the field under study. The research subjects involved were principals, teachers and students in grades IV, V and VI. The data collection techniques used are data collection techniques through interviews, observations and documents. Furthermore, the data analysis method uses several steps of data analysis in qualitative research, namely data reduction, data display, and data conclusion drawing / verification. While the data validity techniques used are extending the observation period, increasing persistence, triangulating data and discussing with others The results of the research and discussion show that: 1) The role of teachers in implementing multicultural education in developing tolerance attitudes can be done by building mutual respect, mutual appreciation, empathy, courtesy, brotherhood and caring attitudes. 2) Supporting and inhibiting factors in the application of multicultural education. The supporting factors are the teacher's understanding of multicultural education and the school environment where students socialize and carry out positive activities that are very supportive in fostering students' tolerance attitudes. While the inhibiting factors are that there are still some students who cannot communicate well, teachers experience a lack of media about diversity in schools such as posters, writings, and pictures that show diversity and multicultural values and the cultivation of multicultural values outside the school environment is still lacking.